Digital euro: Short-term effects on the liquidity of German banks considering holding limits - Benedikt Fritz; Ulrich Krüger; Lui Hsian Wong (Deutsche Bundesbank, 2024)
We examine the impact of introducing a digital euro, as currently conceptualized in the proposal by the European Commission, on the liquidity situation of banks in Germany. The analyses are the basis for assessing the effects of a digital euro on banks' liquidity, as presented in the 11th Annual Report of the German Financial Stability Committee. This paper extensively addresses the technical details of the analyses and substantiates the robustness of the discussed findings. Our analysis focuses on short-term effects. In this environment, deposits are swiftly withdrawn and converted into digital euros, leaving banks with limited opportunities to adapt. We consider a scenario where users fully utilize the holding limit of the digital euro, along with additional scenarios that account for risk-mitigating factors. We employ a unique dataset that combines banking supervisory data with payment transaction information. Our analysis demonstrates that particular savings banks and cooperative banks are vulnerable to retail deposit outflows from exchanges into digital euro. However, only few banks would experience a liquidity shortfall if liquidity in the form of high-quality liquid assets could be redistributed within the banking associations (liquidity balancing). Furthermore, our analysis indicates that based on a holding limit of exteuro3,000 the liquidity shortfall based on the Liquidity Coverage Ratio remains relatively small in aggregate compared to the level of high-quality liquid assets of the entire banking system in all scenarios (up to 2%).
Keywords: G21; G32; G38; 330; Central bank digital currency; holding limits; bank liquidity; systemic risk